Society for Music Teacher Education Professional Literature Project - Music Educators National Conference, Reston, VA.; Heller, George N.; Music Educators National Conference, Reston, VA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1999)
This project aims to correct the somewhat chaotic state of professional literature on music teacher education. First, the project provides a tentative definition of music teacher education and then proceeds to sort, classify, and define the diverse literature. After an introduction, the project is divided into the following sections: (1) "Music Teacher Education Literature in General"; (2) "Music Teacher Education Literature on Conducting"; (3) "Music Teacher Education Literature on Field Work"; (4) "Literature on Elementary Classroom Teacher Education in Music"; (5) "General Music Teacher Education Literature"; (6) "Choral Music Teacher Education Literature"; (7) "Instrumental Music Teacher Education Literature"; and (8) "Literature on Graduate Study in Music Teacher Education." (BT)
Availability: Music Educators National Conference, 1806 Robert Fulton Drive, Reston, VA 22091-4348; tel: 703-860-4000; Web site: http://www.menc.org.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Bibliographies; Choral Music; Elementary Secondary Education; Field Studies; Graduate Study; Higher Education; Music Education; Music Teachers; Teacher Education; Professional Literature; Conducting (Music) -- Instrumental Music; Reference Materials, Bibliographies